Evaluation Model of Islamic Education Learning in Schools in The Digital Age - Nursyamsiyah, Siti (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The COVID-19 pandemic is a challenge for educational institutions in learning and evaluation. However, Luqman Al-Hakim Elementary School implements an online oral and practice evaluation model through a video call to continue producing student outputs with Islamic characters. Students remain motivated and committed to learning to get the best grades. This research is more inclined toward a qualitative approach because it is a natural setting. The subjects of this study consisted of 2 Islamic Religious Education teachers and ten students. Data were obtained in 3 ways: observation, interviews, and documentation. Data analysis using source and method triangulation. The research findings show that the online evaluation model uses videos in practical exams and video calls in Tahfid exams and uses WhatsApp to monitor student progress. Aspects of grade promotion are assessed from the target of memorizing the Qur'an and hadith. One indicator of an increase in grade 2 is that students have remembered Surah An-Naas to Surat Abasa and five hadiths about good morals.